Opening words by Stefán B. Sigurðsson at the 6th NRF Open Assembly. - Stefán B. , Sigurðsson (Arctic Portal, 2011)
Opening words from rector of University of Akureyri, Stefán B. Sigurðsson. UNAK hosted the 6th NRF Open Assembly in Hveragerði Iceland, 4. - 6. September 2011. Please click on the URL below to see the video. Recorded by Arctic Portal.